Energy-transfer versus electron-transfer reactions for the light-harvesting phthalocyanine/ dithiolato-bisimino zinc system. Issue 4 (16th February 2020) - Soliman, Eman; EL-Khouly, Mohamed; Ramadan, Abd El-Motaleb M.; EL-Mehasseb, Ibrahim; Shaban, Shaban Y.
Abstract: In quest of light harvesting systems, the interaction of a dithiolato-bisimino zinc complex, {2, 6-bis(2-mercapto-3, 5-di tert -butylphenylaminomethyl)pyridine zinc(II)} (DBZ) and 1, 4, 8, 11, 18, 22, 25-octabutoxy-29H, 31H-phthalocyanine (Pc) has been investigated by steady-state absorption and fluorescence, as well as time resolved fluorescence techniques in both polar and nonpolar solvents. In nonpolar solvent, the fluorescence of the singlet DBZ (at 390 nm) was heavily quenched accompanied with formation of the singlet state of Pc (at 777 nm), indicating the occurrence of energy transfer from the singlet DBZ to populate the singlet Pc. Based on the fluorescence lifetime measurements of DBZ in the absence and presence of Pc, the rate constant ( k ENT ) and quantum yield ( Φ ENT ) of energy transfer were found to be 2.63 × 10 8 s −1 and 0.47, respectively. By exciting the Pc entity in the presence of DBZ, electron transfer takes place from the electron donating Pc to the electron accepting DBZ in polar acetonitrile. The observed thermodynamic parameters suggest the spontaneity of the binding for DBZ to Pc and the key interacting forces may involve hydrogen bonds, van der Waals forces and π-π stacking. The results suggest that the electron transfer via the singlet Pc is thermodynamically feasible. The difference in behavior in both solvents can therefore be ascribed to the difference in polarity and the nucleophilic character of the solvent, i.e. the donor strength of the coordinated solvent. Graphical Abstract: